Coordination of natural and built infrastructure to better manage extreme events: a hydro-finance modeling framework - Hongkai Gao; Reepal Dinesh Shah; Dai Yamazaki; Theodore J Bohn; Glen Low; John Louis Sabo (Environmental Research Letters)
Natural infrastructure offers a promising, soft-path solution to water security challenges; however, the scientific framework for siting and measuring the efficacy of such restoration projects is nascent. In this paper, we developed a hydro-finance modeling framework to analyze the impact of constructed wetlands on streamflow extremes and cash flow compared to a purely built, or hard path, infrastructure project. Wetlands significantly diminished the flood peak but had variable—and often negative effects—on baseflow. By contrast, flood peak reduction volumes by wetlands were of adequate size to offset flood pool requirements in downstream reservoirs and meet low-flow targets to sustain manufacturing during the dry season. Net positive cash flow originating from avoided costs of water tariffs offset or exceeded capital costs of modestly sized wetlands built on low value land leading to water security solutions that generate revenue. Building back nature can be profitable.